Paleo-Redox Conditions of the Albian-Danian Carbonate Rocks of the Cauvery Basin, South India: Implications for Chemostratigraphy - Madhavaraju, J.; Hussain, S.; Ugeswari, J.; Ramasamy, Nagarajan; Ramasamy, S.; Mahalakshmi, P. (2015)
© 2015. Elsevier Inc. All rights reserved.To understand the paleo-redox conditions that occurred during the Albian-Danian, we have analyzed major and trace elements from limestone samples collected from three sections of the Cauvery Basin. In the Vadugarpettai quarry section, coral algal limestone (CAL) and bedded limestone show small variations in CaO content (54.4-55.5%; 51.3-54.1%, respectively) than marl and gray shale (GS) (31.9-49.7%; 26.9-40.3%, respectively). In the Vellipirangiyam quarry section, oyster Gryphaea limestone (OGL) shows larger variations in CaO content (42.5-53.9%) than Inoceramus limestone and fossiliferous limestone (52.00-52.50%; 52.70-52.80, respectively). The concentrations of immobile trace elements (Zr and Th) varied significantly between different litho-units of the sedimentary rocks of Albian-Danian age. In addition, Al2O3 shows a positive relationship with immobile trace elements such as Zr and Th, suggesting a terrigenous origin for these elements. Enrichment of U and V contents is higher in the GS and particular intervals of CAL and marl bedded limestone (MBL) of the Vadugarpettai quarry section, lower and upper parts of the OGL of the Vellipirangiyam quarry section, and lower and middle parts of the limestone sequence of the Periakurichchi quarry section. The GS and lower part of MBL (Vadugarpettai quarry section); lower and upper parts of the OGL (Vellipirangiyam quarry section); and lower, middle, and upper parts of the Periakurichchi quarry section also show enrichment of Mo. Furthermore, high values of U/Th were noticed in the CAL and MBL of the Vadugarpettai quarry section, OGL of the Vellipirangiyam quarry section and certain intervals of the Periakurichchi quarry section. Such variations in U, V, and Mo contents and the U/Th ratio in the studied sections suggest that the Cauvery Basin experienced oxic to suboxic-anoxic conditions during Albian-Danian.